2020
DOI: 10.3389/fendo.2020.00066
|View full text |Cite
|
Sign up to set email alerts
|

Interfering Role of ERα on Adiponectin Action in Breast Cancer

Abstract: Obesity is characterized by an excess of adipose tissue, due to adipocyte hypertrophy and hyperplasia. Adipose tissue is an endocrine organ producing many bioactive molecules, called adipokines. During obesity, dysfunctional adipocytes alter adipokine secretion, contributing to pathophysiology of obesity-associated diseases, including metabolic syndrome, type 2-diabetes, cardiovascular diseases and many types of malignancies. Circulating adiponectin levels are inversely correlated with BMI, thus adiponectin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 122 publications
(166 reference statements)
0
40
1
1
Order By: Relevance
“…However, steroids and hormonal therapy in a long-term cancer treatment may stimulate the development of diabetes and cardiovascular disease at which older adults, especially with obesity, are at risk [31,32]. Therefore, nutritional research is needed among obese older cancer patients to establish prognosis of the disease course [33].…”
Section: Nutrition Aging and Cancer In The Elderlymentioning
confidence: 99%
“…However, steroids and hormonal therapy in a long-term cancer treatment may stimulate the development of diabetes and cardiovascular disease at which older adults, especially with obesity, are at risk [31,32]. Therefore, nutritional research is needed among obese older cancer patients to establish prognosis of the disease course [33].…”
Section: Nutrition Aging and Cancer In The Elderlymentioning
confidence: 99%
“…Adiponectin, also known as an adipocyte complement-related protein of 30 kDa (Acrp30), was first discovered in 1995 [ 16 ], while three other independent research groups also identified adiponectin as AdipoQ [ 17 ], adipose most abundant gene transcript 1 (apM1) [ 18 ] and gelatin-binding protein of 28 kDa (GBP-28) [ 19 ] using different approaches. Human adiponectin is a 244 amino acid protein that consists of an amino (NH2)-terminal signal sequence, a variable region, a collagenous domain and a carboxy (COOH)-terminal globular domain ( Figure 2 ) [ 16 , 20 , 21 ]. Adipocytes secrete adiponectin into the bloodstream as three oligomeric complexes, including a low-molecular-weight (LMW) trimer (~60 kDa), a medium-molecular-weight (MMW) hexamer (~150 kDa), and a high-molecular-weight (HMW) multimer (~420 kDa), which are formed via a series of complex signalling and modification processes [ 20 , 21 ].…”
Section: Adiponectinmentioning
confidence: 99%
“…Human adiponectin is a 244 amino acid protein that consists of an amino (NH2)-terminal signal sequence, a variable region, a collagenous domain and a carboxy (COOH)-terminal globular domain ( Figure 2 ) [ 16 , 20 , 21 ]. Adipocytes secrete adiponectin into the bloodstream as three oligomeric complexes, including a low-molecular-weight (LMW) trimer (~60 kDa), a medium-molecular-weight (MMW) hexamer (~150 kDa), and a high-molecular-weight (HMW) multimer (~420 kDa), which are formed via a series of complex signalling and modification processes [ 20 , 21 ]. In its simplest form, adiponectin is a trimer, consisting of three monomers (~28 kDa) that undergo post-translational modifications (hydroxylation and subsequent glycosylation), and is stabilized by disulphide bonds within the collagenous domains of each monomer [ 20 , 22 ].…”
Section: Adiponectinmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK contributes to insulin sensitivity due to an increase in glucose uptake in insulin sensitive organs, but, unlike leptin, adiponectin is reduced in obese subjects, thus its anti-inflammatory, anti-proliferative and pro-apoptotic effects are compromised in this population [ 127 ]. Solid tumours present adiponectin receptors [ 128 ] and studies with MCF-7 human breast cancer have indicated positive apoptotic response effects via p53 are modulated by AMPK phosphorylation induced by adiponectin [ 129 , 130 ] specially in ERα negative cancer [ 130 , 131 , 132 ]. Besides that, adiponectin is able to inhibit the activity of an enzyme responsible for estrogen production, aromatase, one of the major risk factors for breast cancer development in postmenopausal women [ 90 ].…”
Section: Adipose Tissue and Cancer: Linked By Inflammationmentioning
confidence: 99%